Planejamento e gestão metropolitana de Belo Horizonte: a construção de uma política pública - Ana Carolina Utsch Correa (2013)
The Metropolitan Region of Belo Horizonte (RMBH) is the focus of this work: it shows us an arrangement that has failed in the past for not having recognized the inequality of power between their parts, recovers recently and prepares a new arrangement that has been shown stable. But how is this arrangement, what its aims and what its scope? The question arises because it turns out that the early years of renewed arrangement of RMBH were uncoordinated in their activities: the State Secretariat for Regional and Urban Development (Sedru) performed a set of activities and the recent Metropolitan Development Agency (Agency RMBH ) performed other, without interacting, although some actions were complementary. In the next government, the entire metropolitan issue moves to the new Extraordinary State Secretariat of Metropolitan Management (SEGEM) and Agency RMBH, focusing on other new projects. What state, municipalities and civil society expect this coordination effort? The research sought to recover the historical formation of the metropolitan issue, from the urban reform, then focusing on the creation of the Metropolitan arrangement of Belo Horizonte, through the revision of the legislation on the subject and current documents,to update this information by interviews with key metropolitan actors. Understanding these issues is to understand how metropolitan actors perceive and alter the metropolitan region of Belo Horizonte, a strategic location for its socioeconomic and political aspects.